Toxicity of Porella chilensis Sesqui- and Diterpenoids against Larvae of the Corn Pest Spodoptera frugiperda (J.E. Smith) (Lepidotera: Noctuidae) - Corzo, Fernando Livio (2012)
Porella, the largest genus of the family Porellaceae (Hepaticae) is widespread in the tropical and subtropical regions of South America. Most Porella species are rich sources of sesqui- and diterpenoids, many of which show interesting biological activities. Secondary metabolites produced by plants can interact with insects and act as antifeedants and growth regulators affecting hormone and nervous systems as well as stomach and muscle tissues. A previous chemical investigation of a Patagonian collection of Porella chilensis yielded sesqui- and diterpenoids that were now evaluated for their effects against Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae), a serious pest affecting corn crops mainly in the Americas. Four pinguisanes (1-4), three fusicoccanes (5-7), and one aromadendrane (8) from P. chilensis displayed larvicidal activity against S. frugiperda when incorporated to the larval diet at 100 and 200 μg/g of diet with a significant decrease in the larval growing rate. The observed effects were in part produced by severe alterations of the epithelial cells of the midgut as indicated by our histological studies.